Metal-catalyzed carbonylation of alkynes: key aspects and recent development. Issue 21 (20th May 2015) - Quintero-Duque, Samuel; Dyballa, Katrin Marie; Fleischer, Ivana
Graphical abstract: Abstract: Carbonyl compounds represent an important class of synthetic intermediates in organic chemistry with growing industrial significance. Among the plethora of methods available for their synthesis, metal-catalyzed carbonylations constitute one of the most prominent ones, due to their efficiency, atom-economy, and often excellent selectivity. Carbonylations of alkynes give access to different types of compounds, such as unsaturated carboxylic acid derivatives or various heterocycles. Many of these products are bulk chemicals, biologically active compounds, or intermediates in the total synthesis. In recent years, considerable progress was made in this field, especially with commercial catalysts based on palladium, rhodium, and cobalt.